O efeito da desintegrina DisBa-01 e do silenciamento da integrina avB3 e na interação de células tumorais e endoteliais in vitro - Durante, Araceli Cristina (2013)
Metastasis depends on several physiological processes such as cell adhesion, transendothelial cell migration and proliferation. These events are mediated mostly by integrins, which are adhesion receptors present on cell surface and responsible for cellextracellular matrix (ECM) binding. Disintegrins are small proteins from snake venoms, known to inhibit integrin action and therefore metastatic events such as transendothelial cell migration. DisBa-01 is a recombinant RGD disintegrin from Rhinoceraphis alternatus venom gland, with high affinity to the v3 integrin and anti-metastatic activity in vivo. Thereby, the aim of this work was to investigate the effect of v3 integrin in cell transendothelial migration and cell adhesion under flow of MDA-MB- 231 tumor cell line using DisBa-01 as v3 integrin antagonist. The 3 subunit was knockdown by 1uL siRNA/ITGB3 and lipofectamine 2000 (Invitrogen) was used as transfection agent. Additionally cell adhesion under flow, transendothelial migration and time lapse assays were performed using MDA-MB-231 cell line (silenced or not) incubated with 10, 100, 500 and 1000nM of DisBa-01. The 3 integrin knockdown and treatments with DisBa-01 at 500 and 1000nM significantly inhibited cell adhesion as well as the transendothelial migration. The interaction between DisBa-01 and tumor cells was visualized only with 1000nM of disintegrin and not silenced cells. Therefore, it is important using DisBa-01 in different cell lines and in vivo to elucidate more aspects of its effects as anti-metastatic drug.